2007
DOI: 10.1111/j.1525-1594.2007.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Metabolic Changes During Exercise in Calves With Total Artificial Hearts of Different Sizes yet Similar Output

Abstract: To evaluate the effects of downsizing of the total artificial heart (TAH), we compared the anaerobic threshold (AT) values in calves with two different types of TAH (Cleveland Clinic-Nimbus TAH and the downsized MagScrew TAH). Exercise studies were performed using a treadmill in 12 calves. During the exercise, parameters to obtain the AT were measured. To evaluate the determinants of the AT, a linear regression analysis was performed between AT and potential variables. AT values from 29 studies revealed no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We have also drawn on 20 years of experience in pulsatile TAH design incorporating basic design requirements for providing systemic flows, implantability, and inherent passive balancing of the left and right flows 17-35. The CFTAH design, however, is extremely innovative, exploring radical new concepts in TAH design in the use of a speed modulated, single shaft, dual centrifugal pump without the use of valves and sensors for control, which greatly decreases the pump size and improves system reliability.…”
Section: Discussionmentioning
confidence: 99%
“…We have also drawn on 20 years of experience in pulsatile TAH design incorporating basic design requirements for providing systemic flows, implantability, and inherent passive balancing of the left and right flows 17-35. The CFTAH design, however, is extremely innovative, exploring radical new concepts in TAH design in the use of a speed modulated, single shaft, dual centrifugal pump without the use of valves and sensors for control, which greatly decreases the pump size and improves system reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Keiji Kamohara et al. (37) of the Cleveland Clinic (Cleveland, OH, USA) evaluated the effects of downsizing of the TAH and compared the anaerobic threshold (AT) values in calves with two different types of TAH (Cleveland Clinic‐Nimbus TAH and the downsized MagScrew TAH). AT values from 29 studies revealed no significant differences between the two different TAHs, with no significant differences in hemodynamic or oxygen metabolic parameters.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%